Metastatic sarcomatoid renal cell carcinoma treated with immune checkpoint inhibitors. (3rd August 2019) - Hanif, Ahmad; Pandey, Manu; Khan, Sumera; Attwood, Kristopher; George, Saby
ABSTRACT: Introduction : Renal cell carcinoma (RCC) with sarcomatoid component carries a poor prognosis. Immune checkpoint inhibitors (CPIs) have been approved for the treatment of metastatic RCC, but their efficacy in patients with sarcomatoid component is not known. Materials and Methods : We conducted a retrospective chart review of 30 consecutive patients at our center who were treated for metastatic RCC with sarcomatoid component. Results : Ten patients were treated with CPI group while 20 patients were in No-CPI group. There were no significant differences in age, sex, race, and stage at diagnosis between the two groups. After a median follow-up of 35 months, 3 of 10 patients in CPI arm and 5 of 20 patients in No-CPI group were alive. The median overall survival was 33.8 m in immunotherapy group compared to 8.8 m in nonimmunotherapy group ( p = .001). Discussion : In our experience, CPI therapy resulted in better outcomes compared to traditional therapy with molecular-targeted agents or chemotherapy in these patients.